Concurrent training in endurance athletes: The acute effects on muscle recovery capacity, physiological, hormonal and gene expression responses post-exercise - Deakin, G. B. (2004)
The research presented in this thesis examined the issue of the compatibility of strength and endurance training within one training regime, termed concurrent training, in recreational cyclists. Various research designs used in the previous literature resulted in inconclusive findings. The overall aim of this thesis was therefore to examine, in three systematically designed studies, the effects of various components of concurrent training regimes on cycling efficiency and recovery, and to identify some of the mechanisms that may be responsible for the interference or impedance of strength and/or endurance adaptations. STUDY 1 The acute effects of strength training on the recovery of muscle force generating capacity and cycling efficiency, post-training Previous studies on the acute effects of prior endurance exercise on muscle force-generating capacity have shown a reduction in muscle force generating capacity both immediately as well as in the hours post-exercise. The aim of this study was to examine the acute residual physiological effects of strength training on cycling efficiency and muscle force generating capacity three hours, and on blood variables three and 24 hours, post-training. This study consisted of two components: Experiment 1A examined varying intensities (high and low) and modes (weight lifting and hill cycling) of strength training, whilst Experiment 1B examined different durations (30 and 60 minutes) of strength training. In Experiment 1A nine male cyclists (age 23.6 ± 5.1 years) who were doing concurrent strength and endurance training completed a control trial of a discontinuous incremental cycle efficiency test (CE) one-week prior to the completion of three treatment trials over a three-week period. The three treatment trial days consisted of single sessions of 1) lower body strength (S), leg-press 6 sets x 6 repetition maximum (RM), 2) lower body strength endurance (SE), leg-press 6 sets x 20 repetitions (equal work as per S session) and 3) hill cycle (H) training, 6 sets x 20 seconds of cycling at a workload corresponding to twice the work of the S protocol. Three hours following each of the strength training sessions, the subjects completed a cycling efficiency test, at the same time as that in the control day trial during which expired respiratory gases, heart rate (HR), blood lactate (BL) concentration and tympanic temperature (TT), as well as gross (GE) and net (NE) cycle efficiency were measured. Prior to the strength training sessions and the efficiency test, the subjects completed three maximal voluntary kneeextension contraction (MVC) trails in conjunction with three voluntary and involuntary muscle activation (MA) trials using a twitch interpolation technique. Blood specimens were collected prior to and 24 hours post the strength training sessions for the determination of plasma creatine kinase (CK) activity. In Experiment 1B, the week following the completion of Experiment 1A, seven of the subjects completed a fourth strength training protocol (SUL), consisting of upper and lower body exercises: leg-press 6 sets x 6 RM, bench-press 4 sets x 6 RM, and lat pull-down 4 sets x 6 RM. The results of Experiment 1A showed a non-significant trend of higher post-training CK levels after the S protocol compared to the SE and H protocols (p=.194). A significant reduction in MVC mean torque was found three hours post the S protocol (p<.05) but not the SE or H protocols. A reduction in the superimposed and control twitches parallelled those of the MVC torque for all protocols, indicating an element of peripheral fatigue. A greater physiological cost was found during the efficiency test following the S protocol for BL concentration, respiratory responses, and TT, as well as greater reductions in gross-body-mass (GBM), GE and NE compared to the efficiency test after the other training protocols. However, HR showed a significantly higher response (p<.05). The results of Experiment 1B showed significant (p<.05) increases in CK for the S and SUL protocols but not the SE and H protocols. No significant difference was found between the four training protocols for mean MVC torque or MA. However, the SUL, S and H protocols all recorded significant (p<.05) changes in mean torque when the respective reductions are expressed as a percentage of the pre-values, compared to the SE protocol. The SUL protocol showed a consistently higher physiological cost of cycling compared to the other protocols. It was concluded that the highintensity S protocol had a greater residual effect on muscle force generating capacity and the physiological cost of cycling than the low-intensity SE protocol when equated for work volume. Further, that the 60-minute high-intensity SUL protocol had a greater residual physiological effect than the 30-minute high-intensity S protocol of similar intensity but a similar effect on the recovery of force generating capacity. It was also concluded that conventional high-intensity strength training had a greater physiological effect on cycling exercise than hill cycling strength training. STUDY 2 The acute effect of the sequence of strength and endurance training on muscle force generating capacity and cycling performance, post-training. The aim of this study was to examine the acute residual physiological effects of two sequences of strength and endurance training completed on the same day on muscle force generating capacity and cycling efficiency three hours post-training and blood variables three and 24 hours post-training. Eight male cyclists (age 23.9 ± 5.6 years) who were doing concurrent strength and endurance training completed a control day with no training sessions, followed by two sequence days, weight/cycle (WC) and cycle/weights (CW), in random order over a three-week period. The 60-minute weight (W) training session was identical to that used in Experiment 1B of Study 1 for the SUL protocol, whilst the cycle (C) session consisted of 60-min of loaded cycling at 60% of VO2 max on a cycle ergometer. The training sessions were separated by a period of three hours. Three hours following the second training session the subjects completed a cycling efficiency test at the same time as that in the control day trial. The same physiological variables were measured during the C training session and the efficiency tests as outlined for Study 1. Prior to each training session as well as the efficiency test, the subjects completed three MVC knee-extension and MA trials as described for Study 1. Blood specimens were collected prior to, immediately following and 24 hours post each training session for the determination of resting and post-training BL and plasma CK activity. Serum testosterone and cortisol concentrations were also determined from pre-training and - efficiency test blood specimens. The results indicated a higher pre (p<.05) and post BL concentration for the W session of the CW sequence compared to the WC sequence, respectively. Respiratory rate, HR, BL, minuteventilation, VO2, TT and NE were all higher whilst GE was notably lower during the C session of the WC sequence compared with the CW sequence. No significant difference was found between the two sequence days for CK. The W session of the CW sequence produced a similar reduction in peak and mean knee-extension torque to that of the WC, respectively. In contrast, the C session of the WC sequence showed a greater reduction in peak and mean torque than that found for the CW sequence, which showed no change in peak and < 1.5% reduction in mean torque, resulting in a significantly greater reduction (p<.05) of -8.28% from pre-training to three-hour post-training for the WC sequence compared to the CW sequence. No significant difference was found between the three trial days for MA. However, a reduction in the superimposed and control twitches parallelled those of the MVC torque for both the WC and CW sequences. The WC showed greater changes than the CW across the majority of the variables measured during the efficiency test. A significantly lower (p<.05) post-training testosterone concentration was found for the CW compared to the WC sequence. A significant reduction (p<.05) in cortisol was found for the WC and CW sequence days compared to the control day and a lower post-training testosterone/cortisol (T/C) ratio was found for the CW compared to the WC sequence. It was concluded that there was an increased physiological stress during those sessions completed second in the training sequence compared to when they were completed first, irrespective of the type of training. Further, it was concluded that the recovery of force generating capacity and physiological parameters following the training sessions are dependent on the sequence of training, with the sequence WC requiring a greater recovery period than the CW. STUDY 3 The effect of the sequence of strength and endurance training on hormonal and gene expression responses and muscle glycogen content post-training There have been limited investigations of the mechanisms for the possible impedance of strength and endurance development. The aim of this study was to determine whether the sequence of completing strength and endurance training sessions on the same day affected hormonal responses and skeletal muscle gene expression as well as muscle glycogen content post-training. Eight male weight-trained cyclists (age 26.1 ± 2.4 years) completed four trial days over a five-week period: single weight (W) and endurance cycle (C) training and two sequence days, WC and CW. The 60-minute W training session consisted of three exercises: leg-press 6 sets x 6 RM, leg-curl 4 sets x 6 RM, and leg-extension 4 sets x 6 RM. The C training consisted of 170 minutes of cycling at 60% of VO2 max. The sequence day training sessions were separated by a period of three hours. Blood and muscle specimens were collected before and after each training session for determination of BL and plasma testosterone and cortisol concentrations as well as muscle glycogen content and expression levels of selected genes associated with muscle growth and metabolic function (no muscle specimens were collected on control days). During the W sessions, HR was measured whilst the same physiological variables were measured during the C training session as for Study 2. Higher HR and BL responses were found in those sessions completed second in the training sequences. Higher responses were also found for all variables during the C session for the WC sequence compared to the CW sequence. Furthermore, the respiratory responses of WC progressively increased at a faster rate over the last 60-90 minutes of the 170-minute C session, compared to the relatively stable responses for the CW sequence. A notable reduction in GE and NE for the WC sequence was also found along with a reduction in RER during the C session. A significant difference (p<.05) was found between the pre and post W time points, with the CW sequence showing considerably lower glycogen levels than the WC sequence, respectively due to a significant reduction produced by the prior C session of ~70% from preto post-training. No significant difference was found between the remaining time points. Both sequence days showed temporal increases in testosterone and cortisol following the second training sessions compared to the control days. Even though no significant difference was found between the two training sequences for testosterone or cortisol, the WC sequence showed a greater response post the second training session than the CW sequence. The WC sequence also produced a reduced T/C ratio compared to the CW sequence in the hours following the second training session. The muscle regulatory factor genes, MyoD and myogenin were affected by the sequence of training, responding more to the CW sequence than the WC sequence, especially at the 25 hour post W time point where significant ~5-6 fold increases in mRNA content were found. In contrast, the genes PDK4, HKII, PGC1 and LPL, which are associated with metabolic functions, responded more to the WC sequence than the CW sequence. The remaining genes associated with muscle metabolic function did not respond more to one training sequence than another. It was concluded that the sequence of training affected the expression of some skeletal muscle genes associated with growth and metabolic functions, but did not directly affect the level of muscle glycogen depletion post the training sessions. However, indirectly affected the choice of substrate during the C session of the WC sequence. It was also concluded that the completion of the second bout of training, irrespective of whether it was strength or endurance orientated, altered the testosterone and cortisol responses compared to the single mode training sessions. Further, that the hormonal response was greater for the WC sequence than the CW sequence.